1987
DOI: 10.1111/j.1464-5491.1987.tb00909.x
|View full text |Cite
|
Sign up to set email alerts
|

Sulphonylurea Failure in Type 2 Diabetes: Treatment with a Basal Insulin Supplement

Abstract: Many diabetic patients continue to have hyperglycaemia on maximal sulphonylurea therapy. Five different therapeutic options, with the prime aim of achieving normal fasting plasma glucose concentrations, have been compared in 15 asymptomatic, sulphonylurea-treated type 2 diabetic patients in a randomized crossover study of 8-week periods. In 24 h metabolic profiles the overnight mean (+/- 1SD) basal plasma glucose level on sulphonylurea therapy was 8.9 +/- 4.2 mmol/l. This was slightly improved with added metfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(26 citation statements)
references
References 22 publications
1
24
1
Order By: Relevance
“…The progressive nature of the hyperglycemia seen in type 2 diabetes (3) is exemplified by the evidence herein that 53% of patients with newly diagnosed diabetes treated with sulfonylurea therapy require additional treatment within 6 years to maintain FPG levels Ͻ6.0 mmol/l. A basal insulin regimen was used in this study because it is highly effective in suppressing basal hepatic glucose production (13,14). The overall improvement seen in glycemic control may reflect increased glucose-mediated release potentiated by the sulfonylureas in the setting of adequate basal insulin implementation.…”
Section: Hypoglycemiamentioning
confidence: 99%
“…The progressive nature of the hyperglycemia seen in type 2 diabetes (3) is exemplified by the evidence herein that 53% of patients with newly diagnosed diabetes treated with sulfonylurea therapy require additional treatment within 6 years to maintain FPG levels Ͻ6.0 mmol/l. A basal insulin regimen was used in this study because it is highly effective in suppressing basal hepatic glucose production (13,14). The overall improvement seen in glycemic control may reflect increased glucose-mediated release potentiated by the sulfonylureas in the setting of adequate basal insulin implementation.…”
Section: Hypoglycemiamentioning
confidence: 99%
“…Certain proposed deleterious effects of insulin support the argument that liberal use of insulin should be avoided (Holman et al 1987;Karam 1992;Quatraro et al 1986;Turner et al 1986). Such deleterious effects of insulin include bodyweight gain from increased lipogenesis, increased atherosclerosis (growth factor-like properties, effects on endothelial cell uptake and synthesis of cholesterol, and smooth muscle proliferation) and potentiation of hypertension.…”
Section: Insulinmentioning
confidence: 87%
“…It has been previously reported that the addition of metformin is less effective than the addition of ultralente insulin in NIDDM patients with secondary failure to sulfonylureas (11). Differences in the type of long-acting insulin used (NPH vs. ultralente) and in its dosage (11.7 ± 1.0 U/day in our study vs. 32.5 ± 6.6 U/day in the study of Holman et al [11]) and differences in the sulfonylurea used may explain the contrasting results in the two studies.…”
Section: Phasementioning
confidence: 99%